PENERAPAN METODE INVESTIGASI KELOMPOK (GROUP INVESTIGATION) SISWA SD SWASTA TUNAS BANGSA SAMBIREJO TIMUR KECAMATAN PERCUT SEI TUAN - Ely Handayani (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2021)
The purpose of this study was to determine the application of the Group Investigation Method for Class V SD Swasta Tunas Bangsa Sambirejo Timur, Percut Sei Tuan District, to find out what obstacles were faced by educators when implementing the Group Investigation Method. looking for solutions when facing obstacles faced by educators when implementing the Group Investigation Method for Class V students at SD Swasta Tunas Bangsa Sambirejo Timur, Percut Sei Tuan District. This type of research is descriptive qualitative research. The research subjects were 1 homeroom teacher, 6 female students and 6 male students. The research uses the Group Investigation Method and is carried out using interview, observation and documentation instruments. The results of this study indicate that the application of the Group Investigation Method (Group Investigation) is as follows: Educators divide students into several groups, provide brief directions, encourage each group to choose a chair and note taker, give time to complete assignments and monitor student activities, urge students to presentation in front of the class in turn, evaluating. The obstacle is that it requires more time, requires more focus on students and overcomes student noise. The solution is to use as little time as possible, Educators must focus on monitoring student activities, and observing and warning students to prevent commotion.